ANALYSIS OF FIBER AND PROTEIN LEVELS ON SNACK BAR BASED ON JACKFRUIT (Artocarpus heterophyllus L.) AND FLOUR-BASED FLOUR GREEN BEAN (Vigna radiata L.) - Susilo Yulianto; Alfina Ayu Lestari; Ratih Purwasih (Jurnal Jamu Kusuma, 2023)
Snack bars are alternative foods that can fulfill nutritional needs and can delay hunger. Currently, cheaper local food ingredients are needed, one of which is jackfruit seeds. Jackfruit seeds are generally underutilized, while jackfruit seeds that have been processed into flour have a high protein content. To support the need for fiber content in the snack bar of this study, it is necessary to add nuts such as mung beans. This study was conducted to determine the crude fiber and protein levels in snack bars based on jackfruit seed flour and mung beans. This type of quantitative research with a descriptive research design. Test parameters in this study include organoleptic tests, water content, ash content, crude fiber content, and protein determination qualitatively and quantitatively using the UV-Vis spectrophotometer Lowry method. The organoleptic test of the snack bar ware brown for the color has a distinctive aroma of cake and mung beans and has a sweet taste and soft texture. The qualitative test of the protein snack bar using the Xantoprotein method obtained a positive result marked by the formation of a yellow-orange colored ring. The nutritional content of the snack bar is water content of 18.16 ± 0.025%; ash content of 1.83 ± 0.062%; crude fiber content of 7.67 ± 0.142%; protein content of 9.48 ± 0.015%. Determination of fiber and protein content in snack bars based on jackfruit seed flour and mung beans were appropriate with USDA 25048 parameters.